Validasi Modul Piawai Bergawai untuk Mengurangi Perilaku Berisiko pada Generasi Digital Natives - Verdiantika Annisa; Dessy Pramudiani; Marlita Andhika Rahman (Mahesa Research Center, 2022)
This study aims to conduct a validation on the psychoeducation module of Piawai Bergawai subjected towards the generation of digital natives to reduce risky behaviours. Research and development is the applied method in the form of a module formulation. The module is formulated through 4 (four stages), including 1) collecting information and analysing requirements by referring to digital literacy concept, the characteristics of digital natives, and risky behaviours, 2) formulating the module by constructing activity frameworks, 3) professional judgement by involving six (6) people experts in the module topic, including psychologists, teachers, digital literacy researchers, psychological practitioners in digital company, and 4) the last stage is the model improvement that encompasses the presentation of language and supplementary materials that are familiar and appealing for teenagers. The result of the validity test on the module of Piawai Bergawai is categorized as valid which is indicated by the Aiken score that shifted from 0.708 – 0.875. This means that the module already has valid criteria both in terms of construct, content and module appearance.